Coriolis efect particles segregator (CEPS): the feasibility of scaling up lab‑on‑a‑chip separation - Tan, Yong Zen (2022)
Effective separation is critical in a wide range of applications. The focus here is on disease diagnosis in the healthcare industry and blood constituent separation in the medical industry, whereby lab-on-a-chip devices are generally limited by low throughput, which restricts separation on a practical scale. In this study, we conceive a novel Coriolis Effect Particles Segregator (CEPS), in which Coriolis force is harnessed as the key driving force for separation in a simple milli-fluidic straight-through channel and milliliters (rather than microliters) of fluids can be readily handled. First, Matlab simulations based on theoretical equations prove that perfect separation of 8 and 15 μm particles is possible. Then, Comsol simulations were performed to ascertain if an off-the-shelf milli-fluidic glass tube, coupled with Y-tube fittings as inlets and outlets, can be used. Finally, to provide proof-of-concept, a prototype was designed and built to demonstrate the practical feasibility of the CEPS. In contrast to theoretical calculations, separation was not as perfect, due to pressure differential at the outlets, need to further optimize the operating parameters (e.g., rotation speed, flow rates), adhesion of particles to channel wall, and vibration effects of the assembled setup. This study showcases the feasibility of scaling up the lab-on-a-chip design into a more practical-scale CEPS, providing a new platform for separations particularly of blood constituents (e.g., red blood cells, circulating tumor cells).